Rendimentos e desigualdades de renda no Brasil no periíodo 2004-2012: a contribuição da renda do trabalho da mulher na redução da desigualdade - Melo, Maria Renata Bezerra (2014)
This work aimed to evaluate the contribution of wage income of women in household income and their impact on reducing income inequality in household income per capita in Brazil and in the macro-regions. The database used was the National Sample Survey (PNAD), in the period 2004-2012. To achieve this purpose will be used methodologies for decomposing the Gini index on elements of income proposed by Kakwani, Wagstaff and Doorslaer (1997), as well as the methodology of decomposition of the change in the Gini index, the effect of composition and concentration-effect developed by Hoffmann (2006) and Soares (2006), from the decomposition proposed by Shorrocks (1982). The methodology of Kakwani, Wagstaff and Doorslaer (1997) provides the standard errors, allowing the construction of confidence intervals, being feasible, therefore verify whether changes in inequality were either not statistically significant. The results show that while in the Southeast, South and Midwest the changes from 2004 to 2012 working on the components of man, public welfare and women's work, mainly on the issue of devolution of these budgets were greatly responsible for the fall of Brazilian inequality in the Northeast and North, the income of the Bolsa Família program played a crucial role, especially through - composition effect. Such findings reinforce the importance of economic policies aimed at decentralization of labor income, including income in the context of women's work, as this has a very significant share of income of the households and their dynamics reflects, more significantly, the trajectory towards a less unequal society in terms of monetary income.